APLICAÇÃO DO TVD ASSISTIDO POR BIM NA FASE INICIAL DE UM PROJETO COLABORATIVO - Pereira, Lucas Melchiori; Ferrari, Fernanda Aparecida Marino; Camelo, Gabriela Henriques; Aragão, Danilton Luis Lima de Jesus (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The collaborative design process based on Building Information Modeling (BIM) and Target Value Design (TVD) was discussed from the results of a workshop offered by a post-graduate discipline in Architecture. The aim was to address operational aspects in the adoption of such practices experienced by the project team. The analysis method was the perception triangulation of the professionals involved in concept design activity. The design team intervened in process model defined from the theory, employing the reflection in action. It was concluded that the problem-solution iteration alters the functions importance of the constructive systems during the design concept, which makes inadequate the resources preallocation to comply the client requirements.